PENGENALAN PERKEMBANGAN BATIK TEDJO DI ERA GLOBALISASI - Sulkiah Hendrawati; Rizky Ramadhan; Nining Chaerunisa; Syifa Auras Limayucha (Yayasan Education and Social Center, 2021)
Research conducted using qualitative methods. Qualitative research method is a research method based on the philosophy of postpositivism, used to examine the natural conditions of objects. Based on this research, researchers can conclude: (1). Mr. Tedi sees the prospects to batik is very good, and Mr. Tedi saw in the district there are still not many who use batik uniforms and he is motivated to make his own batik, if in the district using batik he is a business opportunity, (2) The process of making Batik Tedjo, (3) With the Tedjo Batik Company located in Padarincang Subdistrict, Padarincang village has a positive impact on the residents around the company. Residents around the majority of the company work as farmers, with this company, many residents make the job of batik ismoyo as a side job if they are not dying. In addition to having a positive impact on the surrounding residents, schools located in Padarincang Village also felt the positive impact, which provided an opportunity for students at the school to deepen their knowledge of how the process of making batik writing and learning to make batik writing at no cost